Biocultural conflicts: understanding complex interconnections between a traditional ceremony and threatened carnivores in north Kenya - Miquel Torrents-Ticó; Álvaro Fernández-Llamazares; Daniel Burgas; Job Guol Nasak; Mar Cabeza (Oryx, 2023)
Biological and cultural diversity are inextricably linked and rapidly eroding worldwide. As a response, many conservation efforts foster synergies between cultural and biological diversity agendas through biocultural approaches. However, such approaches do not always address biocultural conflicts, where certain cultural practices can lead to biodiversity loss and, in turn, threaten the continuance of such practices. In this study, we examined a biocultural conflict in the Dimi ceremony, the most important rite of passage of the Daasanach agro-pastoralists of north Kenya, in which skins from threatened carnivore species are used extensively as traditional ornaments. We quantified the current use of skins in Dimi as well as changes in the cultural ceremony that exacerbate its impacts on wildlife. We collected field-based data on the context of the use of skins through structured interviews, focus-group discussions, participant observation and counts of skins in two Dimi ceremonies. We counted a total of 121 skins of four carnivore species being used in a single ceremony. We also found that Dimi has become environmentally unsustainable, threatening distant cheetah Acinonyx jubatus and leopard Panthera pardus populations and local species with spotted skins (African civet Civettictis civetta, common genet Genetta genetta and serval Leptailurus serval). The young Daasanach are deeply concerned about the lack of availability of skins in their area, as well as the prohibitive prices, and they are calling for alternatives to the use of skins in Dimi. Overall, our study shows that acknowledging biocultural conflicts and opening space for dialogue with local communities are essential for the maintenance of both biological and cultural diversity.